2022
DOI: 10.3390/coatings12020258
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Carburizing of Laser Powder Bed Fusion Manufactured 316 L Steel for Enhancing the Surface Hardness

Abstract: Austenitic stainless steels produced by laser powder bed fusion (L-PBF) are quite interesting materials owing to their specific microstructure consisting of dendrite walls built of dislocations pinned by many nano-oxides that involves significant strengthening without loss of ductility. In this work, different plasma treatments were performed to harden the surface of 316 L steel manufactured by L-PBF. The samples were characterized by X-ray diffraction (XRD), Raman spectroscopy (RS), light microscopy (LM) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Montanari et al treated 316L stainless steel with L-PBF and modified the steel surface with ion carburization. The results showed that ion carburization generated an Sc phase on the surfaces of the 316L steel and L-PBF-316L steel, which increased the surface hardness by a factor of two and further improved the mechanical properties [16]. Scheuer et al prepared the carburized layer on the surface of AISI 420 martensitic stainless steel and investigated the effect of plasma carburizing time and temperature on their dry sliding friction and wear behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Montanari et al treated 316L stainless steel with L-PBF and modified the steel surface with ion carburization. The results showed that ion carburization generated an Sc phase on the surfaces of the 316L steel and L-PBF-316L steel, which increased the surface hardness by a factor of two and further improved the mechanical properties [16]. Scheuer et al prepared the carburized layer on the surface of AISI 420 martensitic stainless steel and investigated the effect of plasma carburizing time and temperature on their dry sliding friction and wear behavior.…”
Section: Introductionmentioning
confidence: 99%
“…This method offers the advantage of exhibiting a gradual variation in carbon content in the thickness direction due to diffusion from the gas phase to the surface, resulting in reduced interfacial delamination and no changes in the target material's properties under low-temperature heat treatment. Numerous studies have demonstrated the application of this process to enhance the tribological and corrosion performance of austenitic stainless steel, including improvements in scratch resistance, cavitation erosion resist-ance, and other related properties [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…Low-temperature carburizing of stainless-steel materials using carburizing gases, such as methane, propane, and butane, is a common method for producing a carburizing S phase with supersaturated carbon. In this method, carbon diffuses from the surface to form an expanded austenitic phase, thus improving wear resistance similar to the nitriding S phase [30][31][32][33][34][35][36][37]. Furthermore, compared to only carburizing or nitriding, a continuous or simultaneous treatment that combines carburizing and nitriding can increase the thickness, hardness, and wear resistance of the S phase [38][39][40][41][42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…A few papers have reported low-temperature nitriding and carburizing for austenitic stainless-steel fabrication via directed energy deposition and powder bed fusion [22,24,32,46,47]. However, to the best of our knowledge, none of the studies published to date investigate tungsten carbide composites except the previous study [29].…”
Section: Introductionmentioning
confidence: 99%